Casemix, management, and mortality of patients receiving emergency neurosurgery for traumatic brain injury in the Global Neurotrauma Outcomes Study: a prospective observational cohort study. Issue 5 (May 2022) - Clark, David; Joannides, Alexis; Adeleye, Amos Olufemi; Bajamal, Abdul Hafid; Bashford, Tom; Biluts, Hagos; Budohoski, Karol; Ercole, Ari; Fernández-Méndez, Rocío; Figaji, Anthony; Gupta, Deepak Kumar; Härtl, Roger; et al.
Summary: Background: Traumatic brain injury (TBI) is increasingly recognised as being responsible for a substantial proportion of the global burden of disease. Neurosurgical interventions are an important aspect of care for patients with TBI, but there is little epidemiological data available on this patient population. We aimed to characterise differences in casemix, management, and mortality of patients receiving emergency neurosurgery for TBI across different levels of human development. Methods: We did a prospective observational cohort study of consecutive patients with TBI undergoing emergency neurosurgery, in a convenience sample of hospitals identified by open invitation, through international and regional scientific societies and meetings, individual contacts, and social media. Patients receiving emergency neurosurgery for TBI in each hospital's 30-day study period were all eligible for inclusion, with the exception of patients undergoing insertion of an intracranial pressure monitor only, ventriculostomy placement only, or a procedure for drainage of a chronic subdural haematoma. The primary outcome was mortality at 14 days postoperatively (or last point of observation if the patient was discharged before this time point). Countries were stratified according to their Human Development Index (HDI)—a composite of life expectancy, education, and income measures—into very high HDI, high HDI, medium HDI, and low HDI tiers. Mixed effects logistic regression was used to examine the effect of HDI on mortality while accounting for and quantifying between-hospital and between-country variation. Findings: Our study included 1635 records from 159 hospitals in 57 countries, collected between Nov 1, 2018, and Jan 31, 2020. 328 (20%) records were from countries in the very high HDI tier, 539 (33%) from countries in the high HDI tier, 614 (38%) from countries in the medium HDI tier, and 154 (9%) from countries in the low HDI tier. The median age was 35 years (IQR 24–51), with the oldest patients in the very high HDI tier (median 54 years, IQR 34–69) and the youngest in the low HDI tier (median 28 years, IQR 20–38). The most common procedures were elevation of a depressed skull fracture in the low HDI tier (69 [45%]), evacuation of a supratentorial extradural haematoma in the medium HDI tier (189 [31%]) and high HDI tier (173 [32%]), and evacuation of a supratentorial acute subdural haematoma in the very high HDI tier (155 [47%]). Median time from injury to surgery was 13 h (IQR 6–32). Overall mortality was 18% (299 of 1635). After adjustment for casemix, the odds of mortality were greater in the medium HDI tier (odds ratio [OR] 2·84, 95% CI 1·55–5·2) and high HDI tier (2·26, 1·23–4·15), but not the low HDI tier (1·66, 0·61–4·46), relative to the very high HDI tier. There was significant between-hospital variation in mortality (median OR 2·04, 95% CI 1·17–2·49). Interpretation: Patients receiving emergency neurosurgery for TBI differed considerably in their admission characteristics and management across human development settings. Level of human development was associated with mortality. Substantial opportunities to improve care globally were identified, including reducing delays to surgery. Between-hospital variation in mortality suggests changes at an institutional level could influence outcome and comparative effectiveness research could identify best practices. Funding: National Institute for Health Research Global Health Research Group.